DEMAND-SIDE MANAGEMENT: ADAPTATION OF FOREIGN EXPERIENCE TO RUSSIAN CONDITIONS - L. D. Gitelman (Real Economics Publishing House, 2014)
An innovative approach of interaction with consumers of energy companiesis discussed, it is demand-side management technology based on the balance of economic interests. The basic benefits of this mechanism for the subjects of the energy market are presented. Features of demand-side management implementation in foreign countries, including typical barriers and methods for their elimination in the energy companies are set out. The analysis of capabilities and features of the demand-side management in the power of Russia is given.